Exploring Cultural Identity of Senior High School Students through Digital Storytelling “Lutung Kasarung “as Sundanese Folklore - Friatin, Lilies Youlia (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This qualitative research explores the impact of digital storytelling on the cultural identity exploration of Senior High School students using the Sundanese folklore "Lutung Kasarung." The purpose of data collection is to get insight into students' perceptions, experiences, and engagement with their cultural identity through individual interviews and systematic observations. Recurring themes and patterns are revealed through thematic analysis. The study highlights how important it is to create inclusive learning settings and incorporate culturally relevant content. The inclusion of "Lutung Kasarung" successfully piques students curiosity and fortifies their connection to their cultural background. The appreciation of varied viewpoints and cross-cultural understanding are facilitated by collaborative learning. The interviews shed light on the difficulties students have navigating their ethnic identities and participating in festivities of their cultures. By emphasising the benefits of digital storytelling and culturally responsive teaching in assisting students' discovery of their cultural identities, this research advances the field of English education.